1994
DOI: 10.1039/ft9949001307
|View full text |Cite
|
Sign up to set email alerts
|

18O tracer studies of CO oxidation with O2on MoO3. Part 2.—Active sites for CO oxidation with O2and for oxygen isotope exchange between CO2and MoO3

Abstract: Oxygen isotope exchange between C 1802 and MOO, has been examined in connection with the catalytic oxidation of C l60 with "02 on MOO,. Oxide ions at mobile and immobile sites on MOO,, which oxidize CO in the catalytic oxidation, were found to work also as active sites in the oxygen isotope exchange between C 1802 and Mo "03. The observed time dependences of the yields of C 1802, C '*O ' 6O and C ' 602 in the exchange agreed satisfactorily with those calculated from the mobile and immobile site model. In the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…The surface-oxygen concentration was treated as a constant as long as the slope remained constant. The above assumption of a pseudo-firstorder reaction is similar to the one proposed by Lizuka et al 22 and was shown to be efficient in the interpretation of the oxygenisotope exchange between CO 2 and MoO 3 . The rate constant was evaluated by solving the material balance, treating the reactor as an integral reactor where F is the molecular flow, C tot the total concentration, C Os the surface-oxygen concentration, W the amount of catalyst, and y the molar ratios of the respective species tested.…”
Section: Apparent Activation Energies 321 Apparent Ac-tivation Energi...supporting
confidence: 52%
See 1 more Smart Citation
“…The surface-oxygen concentration was treated as a constant as long as the slope remained constant. The above assumption of a pseudo-firstorder reaction is similar to the one proposed by Lizuka et al 22 and was shown to be efficient in the interpretation of the oxygenisotope exchange between CO 2 and MoO 3 . The rate constant was evaluated by solving the material balance, treating the reactor as an integral reactor where F is the molecular flow, C tot the total concentration, C Os the surface-oxygen concentration, W the amount of catalyst, and y the molar ratios of the respective species tested.…”
Section: Apparent Activation Energies 321 Apparent Ac-tivation Energi...supporting
confidence: 52%
“…The surface-oxygen concentration was treated as a constant as long as the slope remained constant. The above assumption of a pseudo-first-order reaction is similar to the one proposed by Lizuka et al …”
Section: Resultsmentioning
confidence: 72%